Relationship between prenatal metals exposure and neurodevelopment in one-year-old infants in the CLIMB study - Xiao-Yuan Fan; Xian-Shu Lin; Bing-Rui Yang; Han-Wen Zhang; Feng Tang; Jia-Jia Tang; He-Bin Chi; Toby Mansell; Noora Kartiosuo; Yin-Yin Xia; Ting-Li Han; Hua Zhang; et al. (Ecotoxicology and Environmental Safety)
Background: Prenatal metals exposure and its effects on infant neurodevelopment have garnered significant attention. However, most studies focus on individual metals, neglecting combined effects. Objectives: We aimed to assess the effects of both single and combined prenatal metals exposure on one-year-old infants’ neurodevelopment. Methods: This study included 189 mother-infant pairs from the Complex Lipids in Mothers and Babies (CLIMB) cohort. The concentrations of 21 metallic elements and 2 metalloids in umbilical cord blood (UCB) serum were measured using inductively coupled plasma mass spectrometry (ICP-MS). Neurodevelopment was measured using Chinese version of Bayley Scales of Infant Development (BSID) for the Psychomotor Development Index (PDI) and the Mental Development Index (MDI). Multiple statistical methods, including linear models, restricted cubic splines (RCS), weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR). Results: After adjusting for potential confounders, prenatal arsenic (As) and strontium (Sr) levels were associated with lower PDI scores (As: β = −2.324; 95 % CI: −4.61, −0.04; Sr: β = −2.426; 95 % CI: −4.67, −0.18) by linear regression, while Sr was associated with lower MDI scores (β = −2.841; 95 % CI: −5.44, −0.25). RCS models revealed nonlinear dose-response relationships between manganese (Mn) and calcium (Ca) with PDI, and for Mn, As, and zirconium (Zr) with MDI. Interactions between certain metals were also identified. Metals mixture had an overall negative effect on both PDI and MDI scores, with Mn being the primary contributor. Conclusion: Prenatal exposure to selected metals or metal mixtures is associated with poorer neurodevelopment in one-year-old infants.